Civilian crime during the British and American occupation of Western Germany, 1945–1946: analyses of military government court records - Kehoe, Thomas J. (European journal of criminology, 2022)
The post-World War II occupation of western Germany remains salient to developing theories of post-war crime, insurgency, and policing during post-conflict reconstruction. Yet there are no quantitative assessments of civilian crime for its first year (1945–6). Different from the Soviet-controlled East, where there is a relatively robust consensus that social and governmental disorder led to prolonged violent criminality, the picture for the western US and British zones is less clear and the literature is disjointed. We address this gap and in so doing help resolve the account of post-war criminality in the west with new data derived from the records of the US and British military government courts. Comparative analyses of crimes against the person, against property, and against civil restrictions were conducted. We employed a historical criminological approach to interpreting these data and to extrapolating their findings to current theories of counterinsurgency, post-conflict policing, and reconstruction. They indicate high rates of petty property crimes, minor civil violations, and limited violent disorder, commensurate with earlier studies of 1947 onwards. We could also better assess contested accounts of social conditions, revealing a more nuanced picture than prior historical analyses. Drawing on criminological, psychological, and counterinsurgency theories, we suggest that economic and social strain forced extensive minor law-breaking that, when combined with intense anxieties, manifested as fear of violent crime. But, importantly, Germans remained confident in the US and British military governments’ ability to ensure security, aiding the west’s recovery.